Census of Publicly Funded Forensic Crime Laboratories, 2014 ([Verlag nicht ermittelbar], 2017)
This data collection contains data from censuses of publicly funded crime laboratories in 2014. The data were collected to examine change and stability in the operations of crime laboratories serving federal, state, and local jurisdictions. The Bureau of Justice Statistics (BJS) first surveyed forensic crime laboratories in 1998, focusing solely on agencies that performed DNA analysis. The National Institute of Justice (NIJ) funded the 1998 study as part of its DNA Laboratory Improvement Program. The BJS' National Study of DNA Laboratories was repeated in 2001. An expanded version of the data collection, called the Census of Publicly Funded Forensic Crime Laboratories, was first conducted among all forensic crime laboratories in 2002. For the 2014 study, data were collected from April 2015 to September 2015 on the organization, functions, budget, staffing, workload, and performance expectations of the nation's forensic crime laboratories operating in 2014. A total of 360 of the 409 eligible crime laboratories operating in 2014 responded to the census. The nation's publicly funded forensic crime laboratories performed a variety of forensic services in 2014, including DNA testing and controlled substance identification for federal, state, and local jurisdictions. The 2014 Census of Publicly Funded Forensic Crime Laboratories obtained detailed information on the types of forensic requests received by these laboratories and the resources needed to complete them. The census also collected data on crime laboratory budgets, personnel, accreditations, and backlogged cases.